Why a Right to Health Makes No Sense, and What Does (Mary Ann Liebert, 2020)
There is a widely held belief in a universal right to the highest attainable standard of health. This essay shows how this right is conceptually unclear, unattainable, and a distraction from a more concrete and attainable right: a right to equitable access to available resources for health (RARH), including equitable access to the social determinants of health. It clarifies conceptual and theoretical issues in the RARH: its underlying theory rooted in historical, economic, and axiological rationales; its concept of component resources and their availability, equity, sustainability; and the redistribution of wealth and power, metrics, and ethics. The advancement of global health equity requires explicit theorizing of what underlies a right to health. The right to the highest attainable standard of health fails in this regard. The RARH provides a desirable, actionable, and measurable foundation for global health equity.